Establishment of a Novel Permissive Cell Line for the Propagation of Hepatitis C Virus by Expression of MicroRNA miR122 - Kambara, Hiroto (American Society for Microbiology, 2012)
The robust cell culture systems for hepatitis C virus (HCV) are limited to those using cell culture-adapted clones (HCV in cell culture [HCVcc]) and cells derived from the human hepatoma cell line Huh7. However, accumulating data suggest that host factors, including innate immunity and gene polymorphisms, contribute to the variation in host response to HCV infection. Therefore, the existing in vitro systems for HCV propagation are not sufficient to elucidate the life cycle of HCV. A liver-specific microRNA, miR122, has been shown to participate in the efficient replication of HCV. In this study, we examined the possibility of establishing a new permissive cell line for HCV propagation by the expression of miR122. A high level of miR122 was expressed by a lentiviral vector placed into human liver cell lines at a level comparable to the endogenous level in Huh7 cells. Among the cell lines that we examined, Hep3B cells stably expressing miR122 (Hep3B/miR122) exhibited a significant enhancement of HCVcc propagation. Surprisingly, the levels of production of infectious particles in Hep3B/miR122 cells upon infection with HCVcc were comparable to those in Huh7 cells. Furthermore, a line of “cured” cells, established by elimination of HCV RNA from the Hep3B/miR122 replicon cells, exhibited an enhanced expression of miR122 and a continuous increase of infectious titers of HCVcc in every passage. The establishment of the new permissive cell line for HCVcc will have significant implications not only for basic HCV research but also for the development of new therapeutics.